RETRACTED: Combination of Tanshinone IIA and Cisplatin Inhibits Esophageal Cancer by Downregulating NF-κB/COX-2/VEGF Pathway - Liao, Xiaozhong; Gao, Ying; Liu, Jiahui; Tao, Lanting; Wang, Dongmei; Xie, Dan; Mo, Suilin (Frontiers in Oncology, 2020)
Cisplatin (DDP) represents one of the first-line drugs used for esophageal squamous cell carcinoma (ESCC) treatment. However, considerable side effects associated with DDP and the emergence of drug resistance are becoming critical limitations for its application. This study aimed to understand whether Tanshinone IIA (Tan IIA) and DDP could generate a synergistic anti-tumor effect on ESCC cells. Both Tan IIA and DDP were demonstrated to inhibit the ESCC cell growth in a time- and dose-dependent manner. When Tan IIA was combined with DDP at a ratio of 2:1, they were observed to present a synergistic inhibitory effect on ESCC cells. The combination treatment was shown to impair cell migration and invasion abilities, arrest cell cycle in the S and G2 phases, and induce apoptosis in HK and K180 cells. Molecular docking algorithms predicted that Tan IIA and DDP could be docked into identical active sites and interact with different residues within the tested proteins. In all of the treated groups, the expression levels of E-cadherin, β-catenin, Bax, Cleaved Caspase-9, P21, P27, and c-Fos were found to be up-regulated, while the expression levels of Fibronectin, Vimentin, Bcl-2, Cyclin D1, p-Akt, p-ERK, p-JNK, P38, COX-2, VEGF, IL-6, NFκB, and c-Jun proteins were observed to be down-regulated. Among these, the combination of Tan IIA and DDP was found to induce the most significant difference. Our results indicate that Tan IIA functions as a novel option for combination therapy for the treatment of ESCC.